MANAJEMEN DAN KEPEMIMPINAN PENDIDIKAN ISLAM - Ummah Karimah (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M), STIT Islamiyah Karya Pembangunan Paron, Ngawi, Jawa Timur, 2015)
Abstract: Man is essentially a leader on this earth (khalifa fil ard), but when the man had been in charge of all types of professions and demanded their sense of responsibility, then that is where it is from among humans as a leader was chosen to be the figure of a single leader. Being a leader is not only easy matter, because in addition to the need to have the capability must also have the courage, in the sense of daring to confront and provide insight and solutions to various problems faced by mankind. Leadership in education can be interpreted as a human figure can become a driving force in humanizing, for the purpose of education is humanizing. This article tries to illustrate a message of Caliph Ali is, when asked by a friend to the critical question of